3
$\begingroup$

I tried to find the general integrals of the given P.D.E in the yellow box.

And I found $c_1$. But I cannot find another one, say $c_2$.

Please help me finding $c_2$. Thank you.

$$\color{#F3D159}{\boxed{\displaystyle\,\,\color{black}{px(z-2y^2)=(z-9y)(z-y^2-2x^3)}\,\,}} \\ \begin{gather*} P=x(x-2y^2)\\ Q=+y(z-y^2-2x^3)\\ R=z(z-y^2-2x^3) \end{gather*}\\\frac{\mathrm dx}{x(z-2y^2)}=\frac{\mathrm dy}{+y(z-y^2-2x^3)}=\frac{\mathrm dz}{z(z-y^2-2x^3)}\\\frac{\mathrm dy}y=\frac{\mathrm dz}z\implies\ln y=\ln z+\ln c_1\\\boxed{ \frac y z = c_1}$$

$\endgroup$
  • $\begingroup$ Does this question come from the PDE $x(z-2y^2)\dfrac{\partial z}{\partial x}+y(z-y^2-2x^3)\dfrac{\partial z}{\partial y}=z(z-y^2-2x^3)$ ? $\endgroup$ – doraemonpaul Nov 2 '13 at 1:12
  • $\begingroup$ Yes, of course!. I forgot writing the expression of $p$ and $q$. Sorry. Can you help me? Dear @Doraemonpaul $\endgroup$ – user315 Nov 2 '13 at 8:48
3
$\begingroup$

$x(z−2y^2)\dfrac{\partial z}{\partial x}+y(z−y^2−2x^3)\dfrac{\partial z}{\partial y}=z(z−y^2−2x^3)$

$\dfrac{x(z−2y^2)}{z−y^2−2x^3}\dfrac{\partial z}{\partial x}+y\dfrac{\partial z}{\partial y}=z$

Follow the method in http://en.wikipedia.org/wiki/Method_of_characteristics#Example:

$\dfrac{dy}{dt}=y$ , letting $y(0)=1$ , we have $y=e^t$

$\dfrac{dz}{dt}=z$ , letting $z(0)=z_0$ , we have $z=z_0e^t=z_0y$

The remaining problem is how to solve $\dfrac{dx}{dt}=\dfrac{x(z−2y^2)}{z−y^2−2x^3}=\dfrac{x(z_0e^t−2e^{2t})}{z_0e^t−e^{2t}−2x^3}$ .

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.